A self-directed workshop for developing advanced data processing and analysis skills in chemistry using Microsoft Excel - Campbell, CD; Smallwood, ZM; Stewart, MI (American Chemical Society, 2020)
Data-handling, processing, and analysis skills are an integral part of a chemist’s skill set and, more generally, are highly sought by employers. We report a self-directed workshop to develop and advance these key skills using the popular spreadsheet program Microsoft Excel. Making use of its accessible user interface, various contextualized problems relevant to chemistry are introduced, linking theory to practical applications and providing insight and understanding of processes that operate behind-the-scenes in many specialized data processing packages. The workshop has been delivered as a remote exercise for both our first and second year undergraduate cohorts (216 students completed). Students reported a positive impact from the workshop, including the development of a wide range of important skills, the utility for future practical work, and the effectiveness of communication remotely to address their issues.